HUBUNGAN LEGISLATIF DAN EKSEKUTIF DAERAH DALAM PROSES PENETAPAN PERATURAN DAERAH KABUPATEN PARIGI MOUTONG (STUDY KASUS PERDA TENTANG PENETAPAN APBD 2012) - Mas’udin, Mas’udin (Katalogis, 2013)
The problems in this research were: 1) how was the change of correlation between the regional Legislative and Executive in the process of district regulation establishment of Parigi Moutong regarding budget 2012. 2) restricting factors of the change of correlation between the Legislative and Executive in the process of district regulation establishment of Parigi Moutong regarding budget 2012. This research used qualitative methods, in order to obtain in-depth description of regional Legislative and Executive in the process of district regulation establishment. Collecting data by using in-depth interview and documentation. Research location was in regional parliament and local government district Parigi Moutong. The results showed that in the discussion of regional regulation regarding regional budget in 2012 Parigi Moutong faced obstacles in its establishment. ti was caused by some factors such as communication, human resources, disposition, and structure.